Effective control of the emerging PEDV G2-c variant with an inactivated autogenous vaccine - Xu, Huan; Wu, Haichao; Min, Juanjuan; Fu, Ningning; Shi, Ying; Zhou, Ping; Wang, Mingwei; Shi, Ang; Zhou, Yushuang; Chen, Jinhua; Hu, Yuli; Sun, Wen; et al. (Frontiers in Veterinary Science, 2025)
BackgroundPorcine epidemic diarrhea virus (PEDV) is one of the most significant pathogens threatening the swine industry, causing severe economic losses in China. PEDV exhibits a high mutation rate, which may compromise the protective efficacy of currently available commercial vaccines.ResultsThis report describes a PED outbreak occurring from February to April 2025 in a southern Hunan swine farm, resulting in approximately 3,000 neonatal piglet deaths within 1 week of birth. We isolated a PEDV strain (XWF/2025) from infected piglet intestinal contents, which phylogenetic analysis classified within the G2-c subgroup. An inactivated autogenous vaccine using intestinal tissues from infected piglets was rapidly developed, evaluated and administered to all sows in the affected unit. Remarkably, piglet mortality rates decreased significantly within 2 weeks post-vaccination. Serological analysis demonstrated substantial increases in anti-PEDV neutralizing antibody titers following vaccination compared to pre-immunization levels. This represents a successful application of an autogenous inactivated vaccine for emergency PED control, providing a safe and effective approach.ConclusionsOur findings offer valuable insights for combating PED outbreaks through rapid, farm-specific vaccine development.